Effect of Garlic (Allium sativum L.) Supplemented Feed on Survival and Growth of Common Carp (Cyprinus carpio L.) - Muzaffar, Farwah; Ansal, Meera D.; Dhawan, Asha (Indian Journal of Animal Nutrition, 2017)
Garlic (Allium sativum L.) powder was supplemented in the feed @ 0, 1, 2 and 3% level (0, 10,20 and 30 g/kg feed) of common carp (Cyprinus carpio L.) to evaluate its growth promoting efficacy. The studywas carried out in outdoor cemented tanks (80 m2), where common carp fry stocked @ 10000/ha, were fed with control and garlic powder supplemented feeds for 120 days @ 5% of BW during first 45 days and @ 2% BW during last 75 days. Garlic supplementation @ 1, 2 and 3% did not affect water quality, nutrient status and plankton production in any of the garlic fed groups. Although, feed cost increased with increase in garlic supplementation rate but a higher (P